Syrian Society in Revolution and War (2011–2024) (Presses de l’Ifpo, 2025)
In 2011, Syrians broke the wall of silence and rose up against the Assad regime to reclaim their rights to liberty and dignity. But the popular revolution was crushed by a 14-year war with devastating consequences: half a million people killed or wounded, over 150,000 imprisoned or disappeared. Half the population was forced into exile or displaced within the country. Millions of Syrians endured grief, hunger, and torture—and for all, a deep sense of powerlessness in the face of injustice. Yet, despite the destruction and the persistence of daily violence, these years of war also gave rise to immense hope and profound social transformations that transcended questions of identity and religion. New forms of mobilisation, autonomous civic initiatives, solidarities, and expressions of free speech emerged, asserting that the Syrian people are determined to shape their own future.The contributions gathered in this volume bear witness to the pioneering legacy of a decade of revolution and war that has irreversibly transformed Syrian society. Through case studies ranging from self-governance and wartime economies to shifts in domestic life, gender dynamics, and transitional justice, the book explores the scale of political, social, economic, and familial changes that Syria has undergone. These developments are analysed both within Syria and in exile—in Turkey, Lebanon, and Jordan—and are situated within the country’s longer historical trajectory. Long overshadowed by geopolitical and strategic readings of the conflict, Syrian society is placed at the heart of this book, which seeks to uncover the forces driving its struggle for liberation.